Career Prediction of Informatics Engineering Alumni Using Naïve Bayes Algorithm - Nurkholis, Nurkholis; Am, Andri Nofiar. (Internet of Things and Artificial Intelligence Journal, 2025)
Alumni are an important part of education, especially in higher education where alumni can be a reference for the quality of the majors, the more alumni graduates who can get jobs in accordance with their majors, the better the teaching and learning process in the majors, but if the opposite happens, the university needs to evaluate the teaching and learning process so that the students produced can keep up with the times, during the process of finding work in accordance with the alumni's majors. Uin Suska Riau informatics engineering alumni are no exception where analyzing alumni careers is important to be able to improve the quality of Uin Suska Riau in producing alumni who are able to compete in the future. The Naïve Bayes algorithm is a branch of machine learning that can make predictions using classification techniques in predicting the career data of informatics engineering alumni. In the study there was alumni data to carry out the prediction process on career suitability with majors using 275 data and divided into training data and testing data resulting in an accuracy of 75%.